Pengaruh Pemasaraan Media Sosial Pada Niat Beli Ulang Melalui Ekuitas Merek di Industri Kosmetik - Butarbutar, Nabila Turahma Niah; Rimiyati, Hasnah (Indonesian Journal Publisher, 2024)
This research aims to analyze the influence of social media marketing on repurchase intentions through brand equity. The type of data used is primary data obtained through a questionnaire, with measurements using a Likert scale of 5. The criteria used are active students in the Special Region of Yogyakarta, active on social media, following Emina's Instagram and purchasing Emina at least once in the last 6 months. Technique Sampling used non-probability sampling with purposive sampling and collected 200 samples. The research instrument was tested for validity and reliability. The data analysis tool uses Structural Equation Modeling (SEM) using the IBM SPSS Amos version 22.0 program. The results of data analysis explain that social media marketing has a positive and significant effect on brand equity, brand equity has a positive and significant effect on repurchase intention, social media marketing has a positive and insignificant effect on repurchase intention, brand equity is able to fully mediate the influence between media marketing social impact on repurchase intention.